Associations of primiparous pre-pregnancy body mass index and gestational weight gain with cesarean delivery after induction: a prospective cohort study - Lin, Shi; Xie, Chunzhi; Teng, Anyi; Chen, Xiaotian; Li, Yan; Zhang, Yangyang; Zhang, Hui; Sun, Ting (Frontiers in Medicine, 2024)
Objective: The effects of Pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) in primiparas remain unclear. This study examines the associations of pre-pregnancy BMI and GWG with cesarean delivery after induction (CDaI) in primiparous women. Methods: This prospective cohort study included 3054 primiparous women. We recorded pre-pregnancy BMI, first, second, and third trimester weight values, as well as instances of CDaI and other pregnancy outcomes. We analyzed the associations of pre-pregnancy BMI and GWG with CDaI by conducting a multivariate logistic regression analysis after adjusting for covariates, and adjusted risk ratios (aRR) and 95% confidence intervals were reported. Results: We recorded 969 CDaIs. In the vaginal delivery group, each increase of 1 standard deviation in the pre-pregnancy BMI was correlated with a 6% increase in the CDaI risk [aRR (95% CI), 1.06 (1.01-1.11)]. Each increase of 1 standard deviation in the rate of GWG during the entire pregnancy was correlated with a 21% increase in the CDaI risk [aRR (95% CI), 1.21 (1.14-1.29)]. Compared to women with a normal weekly GWG in the second and third trimester, those with slow GWG had a 19% increased risk of CDaI [aRR (95% CI), 1.19 (1.01-1.37)]. The subgroup analysis results showed that increases in pre-pregnancy BMI could increase the CDaI risk regardless of the induction method. Conclusion: High pre-pregnancy BMI, excessive GWG, and rapid first trimester GWG are risk factors for CDaI in primiparous women. Excessive first trimester GWG, may associated with increased risks of CDaI in primiparous women.